Analysis Factors Affecting Consumer Decision Making Toward E-Wallet Continuance Usage Intention: The Role of Trust as Mediator - Dita Dwi Rizkiani; Lintang Nawangsasih; Jessy Valencia; Sambudi Hamali (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2026)
Recent reports from several survey institutions indicate that OVO user rates have declined significantly. This study assumes that this decline is due to users' continued intention to use. For that reason, this research intends to explore the perceived user-friendliness, perceived safety, perceived compatibility, and trust levels among OVO users, along with their intention to continue using the service, with trust serving as a mediating factor. The type of this study is quantitative, with a causal-associative design. The study’s participants were 185 OVO users in the Jabodetabek area, and the data collection method was a survey. The data were analyzed using the PLS-SEM method and WarpPLS 8.0. The findings indicated that trust was influenced by perceived security and perceived compatibility. The findings also indicated that the continuance of usage intention was influenced by perceived ease of use and perceived compatibility. Trust was also shown to positively impact the continuance of usage intention. The findings also indicated that trust mediated the relationship between perceived security and perceived compatibility to the continuance usage intention. The study aims to create a theoretical basis for modeling technology user behavior and to address practical aims related to user trust and the continued use of OVO.